Effects of visual feedback on coherence between human brain and muscle - Mat Safri, Norlaili (2003)
Previous studies of oscillatory interaction between signals of human motor cortex and its peripheral muscle using electroencephalography (EEG) and surface electromyography (EMG) observed rhythmic activities in the frequency band 15-35 Hz. In the present study, we compare three difference reference methods of the EEG recording and investigate the effects of visual feedback (VF) on the oscillatory interaction between human motor cortex and first dorsal interosseous (FDI) muscle.